Yield advantage and reciprocity functions of wheat (Triticam aestivum) + Indian mustard (Brassica juncea) intercropping under varying row ratio, variety and fertility level - SRIVASTAVA, R K; BOHRA, J S; SINGH, R K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter seasons of 1999-2000 and 2000-01 at Varanasi to assess the effect of varying row ratio, mustard variety and fertility levels on various competitive functions in wheat (Triticum aestiwn L .) +Indian mustard (Brassicajurzcea Czern & Coss ) intercropping. Mustard was found dominant and aggressive as compared to wheat. Wheat and mustard under 8: 1 and 5: 1 row ratios proved more remunerative and recorded higher yield advantage than 2: 1 row ratio as judged by land equivalent ratio and relative crowding coefficient. Significantly higher aggressivity (1.034) and competitive ratio (2.245) of mustard was noticed under wheat + ’Vardan’ mustard intercropping which caused drastic reduction in wheat yield. Consequently, the total land equivalent ratio and relative crowding coefficient of the system was markedly higher with ’Sanjucta Asesh’ that gave maximum monetary advantage. Increasing fertility up to highest level correspondingly enhanced competitive ratio and aggressivity of mustard. However, the reverse trend was observed on wheat for these indices. The maximum total land equivalent ratio of 1.085 and net return was observed with the application of 100% recommended fertilizer to both the component crops.